Patients with Asthma Prescribed Once-Daily Fluticasone Furoate/Vilanterol or Twice-Daily Fluticasone Propionate/Salmeterol as Maintenance Treatment: Analysis from a Claims Database - Atsuta, Ryo (Pulm Ther, 2018)
INTRODUCTION: There is a paucity of data describing prescribing patterns and adherence to therapy of inhaled corticosteroids (ICS) in combination with long-acting β(2)-agonists (LABA) in the Japanese population in clinical practice. METHODS: This was a non-interventional, retrospective, cohort study of patients who were prescribed medication for asthma, using data from the Japan Medical Data Center Claims Database. Data from patients aged ≥ 15 years with a prescription of asthma drugs between December 2014 and October 2015 (Day 0, the index date when asthma medication was initiated) were analysed in 12-month pre-index and post-index periods. Part 1 focused on baseline characteristics and epidemiological outcomes in the pre- and post-index period in the overall asthma population, whereas comparing medication adherence [number of prescribed days per year and proportion of days covered (PDC)] between ICS/LABA-naïve patients treated with once-daily fluticasone furoate/vilanterol (FF/VI) and twice-daily fluticasone propionate/salmeterol (FP/SAL) was the primary endpoint in Part 2. RESULTS: Of the available patient data (N = 2,953,652), 28,699 patients were identified as having asthma. ICS/LABA was the main asthma treatment prescribed; 11,167 (38.9%) patients were continuous ICS/LABA users. In ICS/LABA-naïve asthma patients, treatment with once-daily FF/VI was associated with higher medication adherence compared with twice-daily FP/SAL; mean [standard deviation (SD)] number of prescribed days per year was 97.8 (115.9) for FF/VI versus 80.5 (92.7) for FP/SAL (p = 0.04), mean (SD) PDC was 26.7% (31.5) for FF/VI versus 21.9% (24.8) for FP/SAL (p = 0.04). FF/VI was also associated with a lower rate of treatment discontinuation and no difference in use of short-acting beta(2)-agonists or oral corticosteroids compared with FP/SAL. CONCLUSIONS: ICS/LABA was the major prescribed asthma treatment in Japan. Medication adherence was greater with FF/VI, which may indicate that patients are more likely to adhere to once-daily FF/VI versus twice-daily FP/SAL. FUNDING: This study was funded by GSK (study sponsor). STUDY REGISTRATION: GSK Study No. 207264, GSK Study Register site: https://www.gsk-clinicalstudyregister.com/search/?search_terms=207264. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s41030-018-0084-4) contains supplementary material, which is available to authorized users.